Preparation Of Gold Nanoparticles From Helianthus Annuus (Sun Flower) Flowers And Evaluation Of Their Antimicrobial Activities - LINY P; DIVYA TK; BARASA MALAKAR; NAGARAJ B; KRISHNAMURTHY NB; DINESH R (International Journal of Pharma and Bio Sciences, 2012)
Nanobiotechnology has dynamically developed as an important field of modern research with potential effects in electronic and medicine due to growing needs of environmentally benign technologies. Gold nanoparticles have become a significant tool in the development of novel biological and chemical processes. The present study deals with cost effective and environment friendly synthesis of gold nanoparticles using Helianthus annuus flower extract as reducing agent as well as capping agent. UV- visible spectra indicates a strong Plasmon resonance that is located at 550 nm. Presence of this strong broad plasmon peak has been well documented for various Me- NPs with sizes ranging all the way from 2 to 100 nm. Transmission electron microscopy (TEM) analysis showed that the gold nanoparticles are polydispersed and ranged in size from 30-50 nm with an average size of 35 nm. Our results suggest that Helianthus annuus mediated gold nanoparticles could act as an effective antimicrobial agent and prove as an alternative for the development of new antimicrobial agents to combat resistance problem.